Inhibition by fibrates of plasminogen activator inhibitor type-1 expression in human adipocytes and preadipocytes - Zirlik, Andreas; Ernst, Sandra; Leugers, Anne; Willecke, Florian; Sobel, Burton E.; Bode, Christoph; Nordt, Thomas K. (Thrombosis and Haemostasis, 2009)
Plasminogen activator inhibitor type-1 (PAI-1), an established marker and mediator of cardiovascular risk, is produced extensively in adipose tissue. Fibrates are hypolipidemic peroxisome proliferator activated receptor-alpha (PPARα) agonists. Recent laboratory and clinical observations indicate that they are also anti-atherosclerotic. Mechanisms responsible, however, remain to be fully understood. The present study was designed to elucidate modulation of PAI-1 expression in adipose cells by fibrates as a potential mechanism. Expression of PPARα was verified by PCR, immunohistochemistry, and Western blotting. In cultured preadipocytes and adipocytes gemfibrozil and fenofibrate significantly reduced PAI-1 protein expression by up to 55 ± 5% and 34 ± 4% under basal conditions and up to 56 ± 6% and 31 ± 6% under conditions of stimulation of the cells with 40 pM trans-Keywords forming growth factor (TGF)β, respectively. Quantification of mRNA showed that the gemfibrozil-induced effect was at least in part regulated at the transcriptional level. Incubations with non-fibrate PPARα agonists showed similar reductions in PAI-1 expression. The decrease in PAI-1 expression induced by gemfibrozil was inhibited by MK886, a PPARα inhibitor. Furthermore, preadipocytes isolated from PPARα-deficient mice produced significantly more PAI-1 than those from wild-type mice upon stimulation with TGFβ. Finally, fenofibrate reduced PAI-1 expression both in plasma and adipose tissue of hyperlipidemic mice. Our data support the view that PPARα activation down-regulates PAI-expression in adipose cells that may contribute in part to the reduction in cardiovascular mortality seen with fibrates in clinical trials.
Keywords: PAI-1; adipocyte; fibrate; metabolic syndrome; haemostasis